Innovative Climate Risk Management Strategies for Data-Sparse Drylands - Joseph Emanuel Jacob; Worou, Nadine; Faye, Aliou; Whitbread, Anthony M.; Diedhiou, Lamine (2023)
Smallholder farmers residing in drylands represent the demographic most susceptible to the effects of climate change and variability. These individuals often grapple with limited resources, restricted access to credit, and a scarcity of arable land, which exacerbates their vulnerability. Managing climate risks within their production environment is not merely important, but a necessity. This is crucial to guarantee their food security and enhance their livelihood amidst the prevailing and future climate conditions.